1970
DOI: 10.1029/rs005i002p00263
|View full text |Cite
|
Sign up to set email alerts
|

Bistatic Radar Measurements of Topographic Variations in Lunar Surface Slopes With Explorer 35

Abstract: Bistatic radar observations of the lunar surface conducted with Explorer 35 at 2.2 meters have been used to measure the average large-scale (tens to hundreds of meters) lunar slopes. Data obtained for the equatorial band between 70 ø east and west longitude show significant (3'1) regional variations. Unidirectional rms slopes of 2 ø, 3 ø, and 6 ø were obtained for Mare Fecunditatis and Oceanus Procellarum, the central highlands and terra surrounding the crater Alfraganus, and the Censorinus highlands, respecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1972
1972
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Analyses of the lunar observations indicated that fundamental differences in scattering among locales in the maria cannot be accommodated by any single law (Tyler and Simpson, 1970), spurring efforts to extract slope probability density functions from bistatic echoes in a manner free from restrictions on a model law's functional form (Parker and Tyler, 1973;Parker, 1974). Tyler (1979) showed that wavelength-dependent values of rms slopes in the maria, estimated from bistatic, dual-wavelength data, can be understood in terms of the variance of the distribution of surface curvature, which he estimated from photogrammatically determined heights.…”
Section: Scattering Models and Surface Propertiesmentioning
confidence: 99%
“…Analyses of the lunar observations indicated that fundamental differences in scattering among locales in the maria cannot be accommodated by any single law (Tyler and Simpson, 1970), spurring efforts to extract slope probability density functions from bistatic echoes in a manner free from restrictions on a model law's functional form (Parker and Tyler, 1973;Parker, 1974). Tyler (1979) showed that wavelength-dependent values of rms slopes in the maria, estimated from bistatic, dual-wavelength data, can be understood in terms of the variance of the distribution of surface curvature, which he estimated from photogrammatically determined heights.…”
Section: Scattering Models and Surface Propertiesmentioning
confidence: 99%
“…Roughness and slope-probability distri butions measured on positive transparencies of stereoscopic photographs taken by the lunar topo graphic, mapping, and panoramic cameras provide a basis for comparison of the radar and photogrammetric methods. Earlier studies compared the results of the Explorer 35 bistatic-radar experiment with 220-cm wavelength radio transmissions (Tyler and Simpson, 1970) and photoclinometric studies on Earth-based photographs (Tyler and others, 1971). Preliminary studies of lunar surface roughness using stereophotogrammetry began during Apollo 10 and employed Has-D14 FIGURE 8.-Flow lobe in basin north of King for which profiles were measured to obtain thickness of flow.…”
Section: Lunar Surface Roughnessmentioning
confidence: 99%
“…In our case, when reflection of radio waves from the two boundaries of subsurface is significant, the dependence F on the ratio of regolith layer thickness and the wavelength gets the oscillatory character. Figure 3 shows the dependence on the reflection coefficient F as function of the regolith layer thickness for 1 2.7 ε ′ = According to (9), the upper max F and the lower min F envelope curves of the oscillations are determined Figure 3. Dependences of reflection coefficient of radio waves F on a thickness l of the regolith layer.…”
Section: The Reflection Coefficientmentioning
confidence: 99%
“…The reflection coefficient M is connected with regolith and bedrock parameters by the complex relationship (9). Using a digital map of the Moon we choose a relatively flat region, for which the Rayleigh law is correct:…”
Section: Determination Of Ground Parametersmentioning
confidence: 99%
See 1 more Smart Citation